ANALISIS SISTEM PENGISIAN BATERAI PADA ROBOT KENDALI PENGANGKUT SAMPAH - Azhar, Misbahul; Usman, Mukhamad Khumaidi (Nozzle : Journal Mechanical Engineering, 2024)
Abstract -- Motorcycle engine electricity requires a source of electrical energy so that the starter system, ignition system, lighting system, and control system function. The charging system supplies electrical energy to the battery to run (supply) the electrical system on the waste transporter control robot. Taking this into account, this research analyzes the battery charging system on the waste transport control robot. The results of the research are charging voltage and electric current coming out of the kiprok and entering the battery with a testing time of 2 minutes at 1200 rpm to 1500 rpm with 3 tests.